Performance and Virulence of the Entomopathogenic Fungi Beauveria bassiana Grown in Media Derived from Biodegradable Agricultural Wastes Enriched with Cricket Powder - Aminudin Afandhi; Rina Rachmawati; Huurul Ainindya Ulihta Zain; Muhammad Akhid Syibâ€™li (AGRIVITA, Journal of Agricultural Science, 2023)
Entomopathogenic fungi (EPF) can be an eco-friendly alternative to control pests. To produce large-scale EPF requires underused economical substrates containing high carbon and nitrogen; hence the production could be cost-effective. This study investigates the effects of organic agricultural waste, i.e., rice bran, rice husks, tea dregs, and wheat bran enriched with cricket powder as culture media on the mycelial growth, sporulation, and conidia viability of Beauveria bassiana and the fungal pathogenicity towards Spodoptera litura larvae. For each type of medium, five independent cultures of B. bassiana are treated as replications. B. bassiana grown on a Â PDA medium is treated as a control. This study shows that rice bran enriched with cricket powder became the most suitable waste medium to support the mass production of virulent B. bassiana. Therefore, rice bran media enriched with cricket powder can be used as an appropriate medium for the mass production of B. bassiana.